Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/8321400
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Smooth Muscle and Cancer Cell Proliferation by New VEGFR Inhibitors and Their Immunomodulator Effect: Design, Synthesis, and Biological Evaluation

Abstract: Abnormal vascular smooth muscle cell (VSMC) proliferation has an important role in the pathogenesis of both atherosclerosis restenosis and hypertension. Vascular endothelial growth factor (VEGF) has been shown to stimulate VSMC proliferation. In addition, angiogenesis is one of the hallmarks of cancerous growth. VEGF is the key modulator for the initial stages of angiogenesis that acts through the endothelial-specific receptor tyrosine kinases (VEGFRs). VEGFR-2 blockage is a good approach for suppression of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…Comparing the in vitro anti-proliferative activity of compound D-1 (the most active member) with the previously published lead compounds 21 , indicated that compound D-1 showed a higher cytotoxic effect against HCT-116 and HepG-2. The cytotoxicity of our published compounds were ranging from 1.94 to 31.70 µM against HCT-116 and from 2.23 to 31.45 µM against HepG-2.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Comparing the in vitro anti-proliferative activity of compound D-1 (the most active member) with the previously published lead compounds 21 , indicated that compound D-1 showed a higher cytotoxic effect against HCT-116 and HepG-2. The cytotoxicity of our published compounds were ranging from 1.94 to 31.70 µM against HCT-116 and from 2.23 to 31.45 µM against HepG-2.…”
Section: Resultsmentioning
confidence: 89%
“…The pyridine-based derivatives A-1, B-1, C-6, and D-1 were synthesised according to the reactions illustrated in Scheme 1 . Nicotinic acid 2 underwent a chlorination reaction with thionyl chloride to give nicotinoyl chloride 3 21 . Nicotinoyl chloride 3 was then reacted with 4-aminoacetophenone to afford N -(4-acetylphenyl)nicotinamide 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In continuance of our earlier works in the scope of the design and syntheses of novel anticancer medicines [36][37][38][39][40][41][42][43][44], particularly VEGFR-2 inhibitors [45][46][47][48][49][50][51][52][53][54], thiazolidine-2,4-diones bearing sulfonylthiourea moieties were synthesized to obtain the four keys of VEGFR-2 inhibitors pharmacophoric features (Figure 3) [55][56][57]. The focus of the current study was to utilize the lead modification approach for sorafenib, a potent VEGFR-2 inhibitor, to obtain novel potent inhibitors.…”
Section: As Anticancer Agentsmentioning
confidence: 68%